Detection of parasites in the soil of a park located at low altitude in a city on the coast of Ecuador - Cedeño-Menéndez, Stalin Javier; Rivero-De Rodríguez, Zulbey; Bracho-Mora, Angela; Tumbaco-Fernández, Carlos Eduardo (Kasmera, 2025)
Parasitic infections are related to poor health education, inadequate environmental sanitation and contamination of soil with fecal matter. Soil contamination with zoonotic parasites that are excreted by animals, which are emitted or become infective in the soil, can infect humans and produce clinical symptoms. In order to evaluate the presence of parasites in the soil of a park in a city in Ecuador, data analysis was performed in the EPIINFO 6.0 platform to obtain the number of samples. Fifty soil samples were collected, each sample was processed with Willis and spontaneous sedimentation techniques. In the microscopic analysis, 38% of the samples were positive, the most frequent species was Toxocara canis, with a prevalence of 26%, unidentified nematode larvae 14%, followed by Ancylostoma spp and Trichuris spp with 4% each. Among the protozoa, 6% of unidentified coccidia were detected, and Toxoplasma gondii with 2%. All of the parasitic species found were found in animals and some were zoonotic, which implies a risk of infection for park users who maintain contact with the soil and do not comply with proper hygiene standards